2021
DOI: 10.1111/bjh.17765
|View full text |Cite
|
Sign up to set email alerts
|

Genetic subtype classification using a simplified algorithm and mutational characteristics of diffuse large B‐cell lymphoma in a Japanese cohort

Abstract: Summary Recent large‐scale genetic studies have proposed a new genetic classification of diffuse large B‐cell lymphoma (DLBCL), which is clinically and biologically heterogeneous. However, the classification methods were complicated to be introduced into clinical practice. Here we retrospectively evaluated the mutational status and copy number changes of 144 genes in 177 Japanese patients with DLBCL, using targeted DNA sequencing. We developed a simplified algorithm for classifying four genetic subtypes—MYD88,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…Analysis of NOTCH1-mutant DLBCL NOTCH1-mutant DLBCL cases were ascertained from a compilation of whole exome, whole genome, transcriptome and targeted DNA resequencing data from 4,586 biopsies of nodal and primary extranodal DLBCL, curated from 45 studies (2017; Arthur et al, 2018;Bohers et al, 2018;Braggio et al, 2015;Bruno et al, 2014;Chapuy et al, 2016a;Chapuy et al, 2016b;Chapuy et al, 2018;Chitalia et al, 2019;de Miranda et al, 2014;Dobashi et al, 2018;Dubois et al, 2017;Dubois et al, 2016;Ducharme et al, 2019;Ennishi et al, 2019a;Fontanilles et al, 2017;Franco et al, 2017;Greenawalt et al, 2017;Hattori et al, 2019;Intlekofer et al, 2018;Juskevicius et al, 2017;Juskevicius et al, 2016;Karube et al, 2018;Kataoka et al, 2019;Lacy et al, 2020;Lohr et al, 2012;Ma et al, 2021;Mareschal et al, 2016;Mareschal et al, 2017;Menter et al, 2017;Mishina et al, 2021;Morin et al, 2016;Morin et al, 2011;Morin et al, 2013;Park et al, 2016;Pasqualucci et al, 2011;Ramis-Zaldivar et al, 2020;Rossi et al, 2017;Schmitz et al, 2018;…”
Section: Star+methods Key Resources Tablementioning
confidence: 99%
“…Analysis of NOTCH1-mutant DLBCL NOTCH1-mutant DLBCL cases were ascertained from a compilation of whole exome, whole genome, transcriptome and targeted DNA resequencing data from 4,586 biopsies of nodal and primary extranodal DLBCL, curated from 45 studies (2017; Arthur et al, 2018;Bohers et al, 2018;Braggio et al, 2015;Bruno et al, 2014;Chapuy et al, 2016a;Chapuy et al, 2016b;Chapuy et al, 2018;Chitalia et al, 2019;de Miranda et al, 2014;Dobashi et al, 2018;Dubois et al, 2017;Dubois et al, 2016;Ducharme et al, 2019;Ennishi et al, 2019a;Fontanilles et al, 2017;Franco et al, 2017;Greenawalt et al, 2017;Hattori et al, 2019;Intlekofer et al, 2018;Juskevicius et al, 2017;Juskevicius et al, 2016;Karube et al, 2018;Kataoka et al, 2019;Lacy et al, 2020;Lohr et al, 2012;Ma et al, 2021;Mareschal et al, 2016;Mareschal et al, 2017;Menter et al, 2017;Mishina et al, 2021;Morin et al, 2016;Morin et al, 2011;Morin et al, 2013;Park et al, 2016;Pasqualucci et al, 2011;Ramis-Zaldivar et al, 2020;Rossi et al, 2017;Schmitz et al, 2018;…”
Section: Star+methods Key Resources Tablementioning
confidence: 99%
“…18 It is noteworthy that this study showed a tendency for more frequent non-GCB subtype (28.2%) than previous pediatric reports in BFM (non-GCB; 17.3%) 7 and FAB (non-GCB; 13.9%). 8 Korean and Japanese studies indicated a significantly higher proportion of non-GCB subtype in adults (approximately 55%-69%), compared with previous Western studies, 19,20 because of a lower incidence of follicular lymphoma, which transforms to GCB DLBCL. 21 As follicular lymphoma, not a pediatric-type follicular lymphoma, is quite rare in children, this is not likely.…”
Section: Discussionmentioning
confidence: 78%
“…Many of the key or defining features in the various clusters are already available for testing in some or even most routine settings, since they can be ascertained by a combination of FISH (for BCL2 and BCL6 translocations, and TP53 loss) and targeted mutational analysis (evaluating MYD88 , CD79B , EZH2 , CREBBP , KMT2D , NOTCH1 , NOTCH2 , TP53 , SGK1 , TET2 , and SOCS1 , among others), although it is unlikely that such focused approaches fully capture the complexity of these subtypes. Nevertheless, a simplified 20-gene classifier has been described and has the potential to approximate the LymphGen approach to classify four main subgroups [ 60 ]. Conspicuously, and perhaps surprisingly, (almost entirely) absent as a major variable in the stratification of the different genomic categories of DLBCL is testing for a MYC translocation that has long been a key component of evaluation of this group of lymphomas.…”
Section: Molecular Studies In Mature B-cell Lymphomasmentioning
confidence: 99%